Online Versus Traditional Master of Music in Music Education Degree Programs: Students' Reasons for Choosing. (October 2015) - Albert, Daniel J.
The purpose of this study was to describe the reasons that two matriculated students had for enrollment into either an online or a traditional master of music in music education (MME) degree program. Research questions were the following: (a) What are the reasons each student gave for matriculating into either an online or a traditional MME program? (b) What are these students' perceptions of both types of MME programs? How did those perceptions influence their decisions to matriculate into a respective program, if at all? Reasons for matriculating into a respective program included professional and financial obligations, creating relationships with faculty, perceived flexibility of the online program, and development of musician identity and musicianship. Implications include employing the hybrid course format to create a balance of both types of learning environments. Suggestions for future research include investigating the value that students find in an applied lesson and/or ensemble participation component of an MME program.